1996
DOI: 10.1148/radiology.198.1.8539387
|View full text |Cite
|
Sign up to set email alerts
|

Biliary stones and sludge in liver transplant patients: a 13-year experience.

Abstract: Stones and sludge are relatively infrequent after liver transplantation but are associated with high morbidity. Surgical or interventional radiologic treatments are usually performed. Bile duct stones are usually treated with surgical biliary reconstruction. While debris and bile duct necrosis are due to ischemia from hepatic artery occlusion, sludge may also have an ischemic pathogenesis in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…2,3 BCS is reported to occur in 4%-18% of orthotopic liver transplant (OLT) patients. [4][5][6][7] There have been only 2 reported cases of BCS in nontransplant patients. 8 With respect to OLT patients, BCS is associated with increased morbidity, mortality, and rejection of the graft.…”
Section: See Editorial On Page 1400mentioning
confidence: 99%
“…2,3 BCS is reported to occur in 4%-18% of orthotopic liver transplant (OLT) patients. [4][5][6][7] There have been only 2 reported cases of BCS in nontransplant patients. 8 With respect to OLT patients, BCS is associated with increased morbidity, mortality, and rejection of the graft.…”
Section: See Editorial On Page 1400mentioning
confidence: 99%
“…In the Shah et al 6 series, ischemia factors were present in 70% of cast patients versus 15% of controls. Sheng et al 1 have reported a relatively close association (30% of cases) between the occurrence of hepatic artery thrombosis and sludge formation after transplantation. In the same study involving 53 patients with sludge/casts after LT, the average cold ischemia time was 12.6 hours.…”
Section: Inflammatory Picturementioning
confidence: 94%
“…Types 5 and 6: the bile duct epithelium is greatly damaged, the formed BC and necrosis floss fill in the bile duct; a complete profile cannot be displayed by contrast, only the residual trunk is visible. Cholangiography is believed to be the criterion standard for BC diagnosis, 14,15 showing the filling defect of the biliary tree. In addition, potential BC characters in biliary duct can be estimated.…”
Section: Clinical Manifestations Of Different Pathotypes Of the Biliamentioning
confidence: 99%